Positive Energy Building Definition with the Framework, Elements and Challenges of the Concept - Mia Ala-Juusela; Hassam ur Rehman; Mari Hukkalainen; Francesco Reda (Energies, 2021)
Buildings account for 36% of the final energy demand and 39% of CO2 emissions worldwide. Targets for increasing the energy efficiency of buildings and reducing building related emissions is an important part of the energy policy to reach the Paris agreement within the United Nations Framework Convention on Climate Change. While nearly zero energy buildings are the new norm in the EU, the research is advancing towards positive energy buildings, which contribute to the surrounding community by providing emission-free energy. This paper suggests a definition for positive energy building and presents the framework, elements, and challenges of the concept. In a positive energy building, the annual renewable energy production in the building site exceeds the energy demand of the building. This increases two-way interactions with energy grids, requiring a broader approach compared to zero energy buildings. The role of energy flexibility grows when the share of fluctuating renewable energy increases. The presented framework is designed with balancing two important perspectives: technical and user-centric approaches. It can be accommodated to different operational conditions, regulations, and climates. Potential challenges and opportunities are also discussed, such as the present issues in the building’s balancing boundary, electric vehicle integration, and smart readiness indicators.